2018
DOI: 10.1111/jphs.12236
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of variables associated with medication nonadherence in patients with hypertension

Abstract: Objective Medication nonadherence represents a major barrier to achieve optimal health outcomes in patients with hypertension. The study aim was to identify obstacles to medication adherence in patients with hypertension in Jordan. Methods Socio‐demographic and clinical variables in addition to medication adherence and health‐related quality of life (HRQoL) were assessed for patients attending three major hospitals in Jordan. Multiple logistic regression was carried out to identify predictors of medication non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…The majority of the current study participants (≈ 73%) reported non-adherence to the prescribed medications. The rate of non-adherence reported in the present study is comparable with earlier studies conducted on patients with hypertension (81%) [ 21 ], diabetes (72.5%) [ 20 ], and angina (79.4%) [ 28 ], using the validated Arabic version of the 4-item medication adherence scale in Jordan. The high non-adherence rate reported in this study sheds light on the necessity to develop effective pharmaceutical care intervention programs aimed at improving medication adherence and hence, health outcomes in patients with dyslipidemia in Jordan.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The majority of the current study participants (≈ 73%) reported non-adherence to the prescribed medications. The rate of non-adherence reported in the present study is comparable with earlier studies conducted on patients with hypertension (81%) [ 21 ], diabetes (72.5%) [ 20 ], and angina (79.4%) [ 28 ], using the validated Arabic version of the 4-item medication adherence scale in Jordan. The high non-adherence rate reported in this study sheds light on the necessity to develop effective pharmaceutical care intervention programs aimed at improving medication adherence and hence, health outcomes in patients with dyslipidemia in Jordan.…”
Section: Discussionsupporting
confidence: 88%
“…Patients with strong concerns about medications’ side effects, dependence, and disruption of daily activities are more likely to be non-adherent to the prescribed medications [ 31 ]. Consistent with this finding, previous studies reported that patients who were concerned about the potential side effects of their prescribed medications were found to be more likely to be non-adherent to their medications among patients with hypertension [ 21 , 33 , 34 , 35 , 36 ], diabetes [ 20 ], metabolic syndrome [ 37 ], and COPD [ 36 ]. A previous study found that the most common reason behind statin discontinuance were concerns about side effects, represented as muscle aches and gastrointestinal disorders [ 38 ].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The Morisky scale has been validated in Arabic language, and it has been used to assess medication adherence in patients with different chronic diseases in Jordan such as hypertension and diabetes mellitus …”
Section: Methodsmentioning
confidence: 99%